Flipped Classroom: Revolusi Pengajaran dalam Meningkatkan Partisipasi Siswa - M. Yusuf (Academicus: Journal of Teaching and Learning, 2025)
The flipped classroom has emerged as an innovative approach to modern education, shifting the role of classrooms from teaching spaces to interactive discussion arenas. This study aims to explore the effectiveness of the flipped classroom method in enhancing student participation and learning outcomes. Using a library research method, this study analyzes relevant literature from journals, books, and educational reports. The findings indicate that the flipped classroom enhances student engagement by integrating digital learning resources for pre-class activities and optimizing face-to-face sessions for in-depth discussions and collaborative problem-solving. Strategically, the implementation of this method fosters student-centered learning by encouraging self-regulated study habits and proactive participation. Teachers play a facilitative role, utilizing digital media and structured discussion formats to deepen conceptual understanding. Additionally, structured pre-class assignments, guided reflections, and technology-assisted peer learning emerge as key strategies for maximizing learning efficiency. The study also identifies challenges such as technological disparities and teacher adaptation barriers, recommending increased teacher training and equitable access to digital resources as critical steps for optimizing the model’s impact. The study concludes that the flipped classroom significantly enhances student participation and provides a structured pathway for transforming traditional pedagogies into more dynamic and interactive learning experiences.